Preservation of cellular structure via immersion fixation in brain banking - Garrood, Macy; Thorn, Emma L.; Goldstein, Adam; Sowa, Allison; Janssen, William; Wilson, Alyssa; López, Claudia S.; Shankar, Raakhee; Stempinski, Erin S.; Farrell, Kurt; et al. (Free Neuropathology, 2025)
Immersing the brain in a solution containing formaldehyde is a commonly used method for preserving the structure of human brain tissue in brain banking. However, there are questions about the quality of preservation using this method, as formaldehyde takes a relatively long period of time to penetrate a large organ such as the human brain. As a result, there is a critical need to determine whether immersion fixation is an adequate initial preservation method. To address this, we present exploratory histologic findings from our brain bank following the immersion fixation of hemi-sectioned brain specimens under refrigeration. Using light microscopy, we found that there was no significant change in the size of pericellular or perivascular rarefaction areas based on the postmortem interval (PMI) or on the progression from the outer (frontal cortex) to the inner (striatum) brain regions. Additionally, we did not identify any significant number of ghost cells – a state of late-stage cellular necrosis – in the light micrographs analyzed. Using transmission electron microscopy of tissue from the frontal cortex, we found that synapses could still be visualized, but there was vacuolization and variable degrees of myelin disbanding identified. Using serial section transmission electron microscopy, we found that identified synapses could be traced from one section to the next. Using serial block face scanning electron microscopy, we also found that myelinated axons on 2D images can be traced with high fidelity from one image to the next, even at PMIs of up to 27 hours. Collectively, our data corroborate previous findings that immersion fixation is effective for prevention of cellular necrosis and for visualizing many ultrastructural features in at least the surface areas of the brain. However, how structural preservation quality should best be assessed in brain banking is an open question that depends on the intended research applications.